Neonatal Bloodstream Infection with Ceftazidime-Avibactam-Resistant blaKPC-2-Producing Klebsiella pneumoniae Carrying blaVEB-25 - Charalampos Zarras; Elias Iosifidis; Maria Simitsopoulou; Styliani Pappa; Angeliki Kontou; Emmanuel Roilides; Anna Papa (MDPI AG, 2023)
Background: Although ceftazidime/avibactam (CAZ/AVI) has become an important option for treating adults and children, no data or recommendations exist for neonates. We report a neonatal sepsis case due to CAZ/AVI-resistant blaKPC-2-harboring Klebsiella pneumoniae carrying blaVEB-25 and the use of a customized active surveillance program in conjunction with enhanced infection control measures. Methods: The index case was an extremely premature neonate hospitalized for 110 days that had been previously treated with multiple antibiotics. Customized molecular surveillance was implemented at hospital level and enhanced infection control measures were taken for early recognition and prevention of outbreak. Detection and identification of blaVEB-25 was performed using next-generation sequencing. Results: This was the first case of a bloodstream infection caused by KPC-producing K. pneumoniae that was resistant to CAZ/AVI without the presence of a metalo-β-lactamase in the multiplex PCR platform in a neonate. All 36 additional patients tested (12 in the same NICU and 24 from other hospital departments) carried wild-type blaVEB-1 but they did not harbor blaVEB-25. Conclusion: The emergence of blaVEB-25 is signal for the horizontal transfer of plasmids at hospital facilities and it is of greatest concern for maintaining a sharp vigilance for the surveillance of novel resistance mechanisms. Molecular diagnostics can guide appropriate antimicrobial therapy and the early implementation of infection control measures against antimicrobial resistance.